Effect of Internal Measures of Service Quality on Business Performance: A Case of Hotel Industry In Penang - Din, Saari (2005)
Sejarah industri hotel di Pulau Pinang sudah lama bertapak semenjak terdirinya Hotel E&O pada 120 tahun yang lalu.